Molecular Analysis of Human Immunodeficiency Virus Type 1 (HIV-1)-Infected Individuals in a Network-Based Intervention (Transmission Reduction Intervention Project): Phylogenetics Identify HIV-1-Infected Individuals With Social Links - Kostaki, E. G.; Nikolopoulos, G K; Pavlitina, E.; Williams, L.; Magiorkinis, G; Schneider, J.; Skaathun, B.; Morgan, E.; Psichogiou, M; Daikos, G L; Sypsa, V; Smyrnov, P.; et al. (J Infect DisJ Infect DisJ Infect Dis, 2018)
BACKGROUND: The Transmission Reduction Intervention Project (TRIP) is a network-based intervention that aims at decreasing human immunodeficiency virus type 1 (HIV-1) spread. We herein explore associations between transmission links as estimated by phylogenetic analyses, and social network-based ties among persons who inject drugs (PWID) recruited in TRIP. METHODS: Phylogenetic trees were inferred from HIV-1 sequences of TRIP participants. Highly supported phylogenetic clusters (transmission clusters) were those fulfilling 3 different phylogenetic confidence criteria. Social network-based ties (injecting or sexual partners, same venue engagement) were determined based on personal interviews, recruitment links, and field observation. RESULTS: TRIP recruited 356 individuals (90.2% PWID) including HIV-negative controls; recently HIV-infected seeds; long-term HIV-infected seeds; and their social network members. Of the 150 HIV-infected participants, 118 (78.7%) were phylogenetically analyzed. Phylogenetic analyses suggested the existence of 13 transmission clusters with 32 sequences. Seven of these clusters included 14 individuals (14/32 [43.8%]) who also had social ties with at least 1 member of their cluster. This proportion was significantly higher than what was expected by chance. CONCLUSIONS: Molecular methods can identify HIV-infected people socially linked with another person in about half of the phylogenetic clusters. This could help public health efforts to locate individuals in networks with high transmission rates.
Keywords: *Disease Transmission, Infectious; *Genotype; *Social Networking; Adolescent; Adult; Aged; Aged, 80 and over; Cluster analysis; Drug Users; Female; Genotyping Techniques; HIV Infections/*epidemiology/*transmission; HIV-1/*classification/*genetics/isolation & purification; Humans; Male; Middle Aged; molecular epidemiology; Phylogeny; Sequence Analysis, DNA; Substance Abuse, Intravenous/complications; Surveys and Questionnaires; Young Adult